The Correlation of Leadership, Organizational Commitment and Leader Member Exchange on Schools Performance - Khie Khiong (AGUSPATI Research Institute, 2023)
The purpose of this study was to analyze the relationship between leadership and school performance, organizational commitment to school performance, the relationship between leader member exchange and school performance. This research method is quantitative, the data was obtained by distributing online questionnaires through social media to teachers. through the simple random sampling method, the respondents of this study were 340 teachers. Analysis of the research data used structural equation modeling (SEM) with SmartPLS software tools, the questionnaire measurement scale used a Likert scale of 7. The stages of testing the research data were measuring the outer model, testing validity, testing reliability and testing structural models and testing hypotheses. Based on the results of data analysis it was concluded that leadership has a positive and significant effect on performance, Leader Member Exchange (LMX) has a positive and significant effect on performance and organizational commitment has a positive and significant effect on performance. Organizational Commitment has a significant effect on Performance. Organizational commitment is the teacher's loyalty to the organization and a continuous process in which the teacher shows and expresses concern or matters that are important to the organization. teachers who have high organizational commitment will make a major contribution to the company because they want to work as much as possible and behave well in achieving school goals, so organizational commitment affects performance. Work-related behavior, respect for leaders' skills and knowledge, loyalty to one another, and liking for one another can all contribute to the development of LMX. The Leader Member Exchange leadership system in its application can generate feedback between individuals without being affected by social boundaries or strata. Leaders and teachers can communicate regardless of seniority and position so that it can have a positive impact on schools, namely in the form of improving teacher performance.